2017
DOI: 10.1016/bs.vh.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptors Modulation of Anxiety-Like Behavior

Abstract: Estrogens exert profound effects on the expression of anxiety in humans and rodents; however, the directionality of these effects varies considerably within both clinical and preclinical literature. It is believed that discrepancies regarding the nature of estrogens’ effects on anxiety are attributable to the differential effects of specific estrogen receptor (ER) subtypes. In this chapter we will discuss the relative impact on anxiety and anxiety-like behavior of each of the three main ERs: ERα, which has a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 112 publications
(153 reference statements)
1
75
0
3
Order By: Relevance
“…Studies of estradiol administration to ovariectomized rats and ESR1 null mice have shown consistent evidence that ESR1 is involved in anxiety-like behavior in non-human animals. 40 Our finding of an association between ESR1 and anxiety may have implications for our understanding of sex differences in anxiety disorders, which generally show about a 2:1 female predominance, and greater susceptibility to develop PTSD following traumatic events. 41 Although this increased susceptibility is partially explained by sex-specific exposure to certain kinds of traumatic events, there may also be differential biological context provided in part by the role of the estrogen receptor.…”
Section: Discussionmentioning
confidence: 82%
“…Studies of estradiol administration to ovariectomized rats and ESR1 null mice have shown consistent evidence that ESR1 is involved in anxiety-like behavior in non-human animals. 40 Our finding of an association between ESR1 and anxiety may have implications for our understanding of sex differences in anxiety disorders, which generally show about a 2:1 female predominance, and greater susceptibility to develop PTSD following traumatic events. 41 Although this increased susceptibility is partially explained by sex-specific exposure to certain kinds of traumatic events, there may also be differential biological context provided in part by the role of the estrogen receptor.…”
Section: Discussionmentioning
confidence: 82%
“…Numerous studies indicate that perinatal testosterone exposure induces lasting effects on anxiety behaviors and the HPA axis (Bingham, Wang, Innala, & Viau, ; Seale, Wood, Atkinson, Harbuz, & Lightman, ; Seale, Wood, Atkinson, Lightman, & Harbuz, ; Zuloaga et al, ). Furthermore, adult testosterone and estrogens dynamically regulate anxiety‐ and depressive‐like behaviors as well as glucocorticoid release via actions at their cognate receptors (Borrow & Handa, ; Lund, Hinds, & Handa, ; Lund, Rovis, Chung, & Handa, ; Weiser & Handa, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are two classical ERs found in the brain -ERα and ERβ (Hara et al, 2015). Although both are important for cognitive function (Hara et al, 2015), binding to each receptor subtype has different effects on behavior (Borrow and Handa, 2017). ERα is associated with anxiogenesis, because its knockdown via ShRNA produced a decrease in anxiety (Spiteri et al, 2010).…”
Section: Discussionmentioning
confidence: 99%